Loss of quality of life associated with genital warts: baseline analyses from a prospective study. Issue 3 (18th February 2011) - Sénécal, Martin; Brisson, Marc; Maunsell, Elizabeth; Ferenczy, Alex; Franco, Eduardo L; Ratnam, Sam; Coutlée, François; Palefsky, Joel M; Mansi, James A
Abstract : Objective: The quadrivalent human papillomavirus (HPV) vaccine is effective against HPV types responsible for 90% of anogenital warts. This study estimated the quality of life lost to genital warts using the EQ-5D, a generic instrument widely used for applications in economic analyses. The findings are described in terms that are more specific to individuals with genital warts using psychosocial questions adapted from the HPV impact profile, a measure developed for HPV-related conditions. Methods: Between September 2006 and February 2008, 42 physicians across Canada recruited 330 consenting patients 18 years and older with genital warts, either at the first or follow-up visit for an initial or recurrent episode. The quality of life lost associated with genital warts was estimated by the difference between participants' EQ-5D scores and age and gender-specific population norms. Results: The study questionnaire was self-completed by 270 participants who were aged 31.5 years (SD 10.4) on average. The majority of participants were women (53.3%), heterosexual (93.5%) and in a stable relationship (66.0%). Genital warts were associated with detriments in the EQ-5D domains of anxiety/depression, pain/discomfort and usual activities. The absolute difference in the EQ-5D utility score and the EQ-VAS health status between genital warts patients and population norms was 9.9 (95% CI 7.3 to 12.5) and 6.0 (95% CI 4.1 to 7.9) percentage points, respectively. These results did not vary significantly according to patient age, gender, time since first episode or number of episodes. Conclusion: The results suggest that genital warts negatively affect the wellbeing of men and women as reflected by poorer quality of life scores compared with population norms.